Hypnic headache in a young patient (35 years old): a rare entity - Batista, Sabrina Borges; Filho, Amauri Pereira da Silva; Romano, Danielle Cortellazzi Colonna; Nakamura, Gabriela Yumi; Freitas, Melissa Viledela Fernandes; Karpejany, Natália Rebeca Alves de Araújo; Reis, Taianara Sampaio (Headache Medicine, 2024)
INTRODUCTION: Hypnic Headache (HH), known as "Alarm Clock Headache," is a rare primary headache disorder characterized by recurrent episodes that predominantly occur during nighttime sleep. Initially described by Raskin, who reported six cases over nine years, the condition was initially noted to be more prevalent in men. However, current evidence suggests a higher prevalence in women. Though typically associated with patients over 50, there are reports of its occurrence in younger individuals. OBJECTIVE: This case report aims to document and describe the clinical presentation, management, and treatment response of a young patient with HH. The case is significant due to the patient's relatively young age and the intensity and frequency of nocturnal headache episodes. The effective treatment response highlights a promising therapeutic approach for similar cases, enhancing clinical understanding and personalized management of HH in younger patients. CASE REPORT: A 35-year-old female smoker with mild depression has experienced recurrent episodes of headache awakening her from sleep for approximately 14 months. The headaches are diffuse, non-pulsatile, moderate to severe in intensity, lasting 30 to 45 minutes, and resolve spontaneously. There are no associated autonomic changes or focal neurological signs on general, neurological, or imaging examinations (MRI and CT). Treatment with lithium carbonate and melatonin resulted in a significant improvement of approximately 90% in pain intensity within 4 weeks. CONCLUSION: This case underscores the importance of recognizing and managing HH in younger patients, where the condition may be less common but equally impactful on quality of life. Further studies are essential to expand our understanding of this rare neurological condition and explore additional therapeutic options. This report aims to provide valuable insights into the clinical presentation and effective management of HH in younger patients.